The Development of Learning Tools for Students with Comorbid Dyscalculia-Dyslexia - Azhari, Budi; Safrina, Khusnul (SCAD Independent, 2022)
This study aimed to develop learning tools to help children with learning disabilities of comorbid dyscalculia-dyslexia. The learning tools were developed using the 4D model. Each stage of development was conducted based on the materials focused on in this research, namely the topics of recognizing and understanding numbers, sorting numbers, and operating numbers. This study involved 280 students, ages between 7 and 8 years old, from four elementary schools. Students took a series of tests, and 11 students were found with comorbid dyscalculia-dyslexia. The results of this study provided an overview related to the learning tools developed, tested, and implemented in mathematics learning for students with dyscalculia and dyslexia. This finding was indicated by the analysis results of recognizing numbers, sorting numbers, and operating numbers using paired-sample t-tests (p< 0.05). The results showed increased students' essential mathematics ability based on the pretest and posttest scores.